A perspective method of garlic enrichment (Allium Sativum L.) with selenium. (November 2019) - Polyakov, A; Alekseeva, T; Soldatenko, A
Abstract: Obtaining high-quality products is one of the most important tasks of agricultural enterprises of all forms of ownership. Quality indicators are not only organoleptic indicators, but first of all, the chemical composition of the products manufactured. Quality food should contain the necessary macro-and micronutrients in a dose that meets the needs of the human body in them. In this regard, the development of methods for obtaining products containing microelements, in the quantity necessary to ensure the normal functioning of a person is a particularly important area at present. We have found that preplant treatment of chives and vegetative plants with a 0.1% solution of potassium selenite in combination with SAS and DMSO makes it possible to produce bulbs in which the content of selenium exceeds the control by 29.4 and 145.3 times. A similar treatment of cloves and plants with sodium selenite leads to an increase in the selenium content in the bulbs to 8.0 mg/kg and 7.3 mg/kg, or 169.8 and 157.2 times in comparison with the control. The proposed method of enrichment of garlic with selenium allows to improve the qualitative composition of this culture and increase its economic significance.